Influence Of Facility, Discount, Word Of Mouth To Purchasing Decisions And Customer Loyalty: (Study On Customer Of NAV Family Karaoke DR. Soetomo Surabaya, branch) - Etika Murti Purbasari; I Gede Arimbawa (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the influence of marketing including facility, discount, and word of mouth to customer purchasing decision at NAV Family Karaoke Dr. Soetomo Surabaya, branch.The type of research is quantitative. The research data is primary data obtained from the sample with the number of 140 respondents who member in NAV Family Karaoke Dr. Soetomo Surabaya, branch. Sampling technique was done by using questionnaires. The data analysis used is Partial Least Square (PLS). Data processed using SmartPLS 3.The results showed that facility, discount, and word of mouth were affected significant simultaneously and partially to purchasing decision and customer loyaltyThe limitation in the exploration of independent variables which affect the level of consumer purchasing decisions for karaoke. In addition, the use of questionnaires as the technique of data collection occasionally provides inaccurate data to researchers.